Evolutionary degeneration of septins into pseudoGTPases: impacts on a hetero-oligomeric assembly interface - Hussain, Alya; Nguyen, Vu T.; Reigan, Philip; McMurray, Michael (Frontiers in Cell and Developmental Biology, 2023)
The septin family of eukaryotic proteins comprises distinct classes of sequence-related monomers that associate in a defined order into linear hetero-oligomers, which are capable of polymerizing into cytoskeletal filaments. Like actin and ⍺ and β tubulin, most septin monomers require binding of a nucleotide at a monomer-monomer interface (the septin "G" interface) for assembly into higher-order structures. Like ⍺ and β tubulin, where GTP is bound by both subunits but only the GTP at the ⍺-β interface is subject to hydrolysis, the capacity of certain septin monomers to hydrolyze their bound GTP has been lost during evolution. Thus, within septin hetero-oligomers and filaments, certain monomers remain permanently GTP-bound. Unlike tubulins, loss of septin GTPase activitycreating septin "pseudoGTPases"occurred multiple times in independent evolutionary trajectories, accompanied in some cases by non-conservative substitutions in highly conserved residues in the nucleotide-binding pocket. Here, we used recent septin crystal structures, AlphaFold-generated models, phylogenetics and in silico nucleotide docking to investigate how in some organisms the septin G interface evolved to accommodate changes in nucleotide occupancy. Our analysis suggests that yeast septin monomers expressed only during meiosis and sporulation, when GTP is scarce, are evolving rapidly and might not bind GTP or GDP. Moreover, the G dimerization partners of these sporulation-specific septins appear to carry compensatory changes in residues that form contacts at the G interface to help retain stability despite the absence of bound GDP or GTP in the facing subunit. During septin evolution in nematodes, apparent loss of GTPase activity was also accompanied by changes in predicted G interface contacts. Overall, our observations support the conclusion that the primary function of nucleotide binding and hydrolysis by septins is to ensure formation of G interfaces that impose the proper subunit-subunit order within the hetero-oligomer.